Baturraden Adventure Forest (BAF): Alternative Facilities of Outdoor Learning Activity for Physical Education Class - Like Nopita Dwi Pepriyana; Indra Jati Kusuma; Panuwun Joko Nurcahyo; Muhamad Syafei; Kusnandar Kusnandar; Bayu Suko Wahono (Jurnal MensSana, 2022)
Baturraden Adventure Forest (BAF) is one of the representative tourism objects for outdoor learning activities. This study aims to analyze the Baturraden Adventure Forest (BAF) Tourism Object as a learning infrastructure for outdoor activities for physical education subjects. This study used a qualitative method, while data collection was carried out in elementary schools throughout Baturraden District. The research subjects used the purposive sampling technique to include BAF managers, school principals, physical education teachers, and elementary students. The collecting data using observation, interview, and documentation techniques. The data's validity was tested using the data triangulation technique—analysis of the data using the analysis model of Miles and Huberman. The study results based on interviews, observations, and documentation showed that the Baturraden Adventure Forest (BAF) tourism object has relevant infrastructure for outdoor learning activities for Physical Education. In addition, BAF is also relevant for student campsites outbound and recreation for all people. The supporting factors in the Baturraden Adventure Forest (BAF) Tourism Object are seven packages: team building, student outbound, river adventure, riverside camp, paintball, walk-in program, and family camp. Baturraden Adventure Forest (BAF) Tourism Object has a high price of facilities, and not all schools can access the activities due to cost constraints. Conclusion: Baturraden Adventure Forest (BAF) tourism object has appropriate facilities to support outdoor learning activities for Physical Education